DEVELOPMENT OF SETS-BASED CHEMISTRY TEACHING MATERIALS AND STUDENT RESPONSES TO SALT HYDROLYSIS MATERIALS - Adila Mawaddah; Saronom Silaban (Sean Institute, 2022)
This study aims to determine whether the chemistry teaching materials developed have met the BSNP standards and are based on SETS and to determine student responses to the designed teaching materials. The development method refers toADDIE development model which has 5 stages, namely the Analysis, Design, Development, Implementation and Evaluation stages. This research stage is only up to the development stage. The results showed that the chemistry teaching materials that had been prepared had met the BSNP standard based on the results of the material expert validation, the average percentage was obtainedof 86.24% with valid/feasible criteria and based on the results of media expert validation, an average percentage of 84.44% was obtained with valid/feasible criteria. Meanwhile, the results of student responses to the designed teaching materials are very high with an average percentage of 88.33% obtained. Thus the SETS-based chemistry teaching materials on the salt hydrolysis material developed have met the BSNP standard and are suitable for use.n.